Effects of fin shapes and orientations with cyclic heating and cooling on melting and solidification of PCM-filled closed space - Kiyak, Burak; Öztop, Hakan Fehmi; Biswas, Nirmalendu; Cosanay, Hakan; Selimefendigil, Fatih (Elsevier Science Inc, 2025)
Phase-change materials (PCMs) offer an effective way to store and release thermal energy to balance the supply and demand for energy. Both the melting and solidification processes have a major impact on how effectively energy storage works and also it is affected by the thermal conditions of the heating or cooling source. Thermal energy storage systems using (PCMs are often limited by slow melting and solidification rates. The current work explores a novel strategy of cyclic heating and cooling for improving the PCM melting and solidification process combined with variations in fin shapes and orientations, to address these inefficiencies. The fins are heated and cooled following cyclic heating and cooling pattern for three different cycle periods (CP) with same amplitude. As a result, PCM is subjected to cyclic heating and cooling. The finite volume method is employed to analyze the impact of cyclic heating-cooling cycles on PCM performance. An analysis is also conducted on the impact of the relative shape of fins-that is, flat, concave, and convex, positions-vertical and horizontal-on the melting and solidification process under three different cycle periods. By applying a finite volume-based computational approach, the numerical model is solved. It is observed that the overall thermal performance of PCM-based energy storage is modulated by the cyclic heating-cooling arrangements. With this, melting time is reduced by 47.1 % compared to horizontal fin arrangement. When the fin pair is arranged vertically (theta = 0 degrees), with the increase in the cycle period to CP3, the amount of stored energy (during the heating cycle) is about 24.7 %. Similarly, the amount of stored energy recovery (during the cooling cycle) is about 43.6 %. When the fin pair is arranged horizontally (theta = 90 degrees), the amount of energy stored is up to 10 % due to the increase in the cycle periods. Similarly, the amount of stored energy recovery (during the cooling cycle) is about 38.5 %. An improved fin designs, combined with cyclic heating-cooling strategies, present an effective solution to enhance PCM-based thermal energy storage systems.
Keywords: Phase change material (PCM); Melting; Solidification; Fin shape and position; Cyclic heating and cooling; Energy storage